The effect of eight weeks of braitonic training on skill behaviors of autistic children (Revista de Investigaciones Universidad del Quindío, 2023)
Background: Autism is the most common disease in the spectrum of pervasive developmental disorders. The main reason for this research was to find the effect of eight weeks of braitonic training on the skill behaviors of autistic children.Materials and Methods: The present study was quasi-experimental research in terms of applied purpose and research method, which was conducted as a pre-test and post-test. Therefore, among the statistical population of the present study, which included children with autism symptoms aged 6 to 8 years, who were referred to welfare centers in Tabriz for treatment, 30 people were selected voluntarily and randomly selected in two groups of 15 people who underwent braitonic and control. Before completing the exercises, the Garz questionnaire was completed by parents. The experimental group performed Braitonic exercises under the supervision of a braitonic instructor and a psychologist in one of the multi-purpose halls of Tabriz for two sessions of 45 minutes a week for 2 months. The control group engaged in their daily activities. After the training program (post-test), both experimental and control groups were measured and completed the Garz questionnaire by parents. For inferential analysis of data SPSS 21 software at p≥0.05 as a significant level was used. Analysis of variance in repeated measures and t-tests was taken to find data.Results: Findings showed that eight weeks of braitonic training has a significant effect on the coordination, agility and reaction of children with autism.Conclusion: braitonic exercises can have a significant positive effect on the motor skills of autistic children.
Keywords: braitonic; skillful behaviors; coordination; agility